2021
DOI: 10.7150/ijbs.50003
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles of m6A modification in liver carcinogenesis

Abstract: The 'epitranscriptome', a collective term for chemical modifications that influence the structure, metabolism, and functions of RNA, has recently emerged as vitally important for the regulation of gene expression. N 6 -methyladenosine (m 6 A), the most prevalent mammalian mRNA internal modification, has been demonstrated to have a pivotal role in almost all vital bioprocesses, such as stem cell self-renewal and differentiation, heat shock or DNA damage response, ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 181 publications
(371 reference statements)
0
21
0
Order By: Relevance
“…Alcohol could induce liver inflammation and oxidative stress cause DNA damage in hepatocytes; ultimately promote tumour initiation and progression [22]. Previously, m6A methylation was reported to play a promoting role in the occurrence and development of HCC, regulating cell proliferation, cell invasion and epithelial to mesenchymal transformation [23]. The levels and activities of m6A regulatory genes YTHDF2, ALKBH5 and FTO can inhibit the HCC malignancy [24][25][26].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Alcohol could induce liver inflammation and oxidative stress cause DNA damage in hepatocytes; ultimately promote tumour initiation and progression [22]. Previously, m6A methylation was reported to play a promoting role in the occurrence and development of HCC, regulating cell proliferation, cell invasion and epithelial to mesenchymal transformation [23]. The levels and activities of m6A regulatory genes YTHDF2, ALKBH5 and FTO can inhibit the HCC malignancy [24][25][26].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…However, most of the m6A measured in total RNA is in rRNA, which is generated by different enzymes. For example, m6A in structural RNAs and U6 snRNAs can be methylated by METTL16, and METTL5 mediates m6A modification of 18 S rRNA and participates with ZCCHC4 in 28S rRNA modifications ( Pan et al, 2021 ). We attempted to measure m6A in mRNA in heart tissue but could not isolate enough purified mRNA after two rounds of polyA selection for m6A RNA quantification using an ELISA-based protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Wealth of recent studies have revealed that circRNA and m 6 A modification exert a regulatory function in different diseases, and many of them highlighted a role in various cancer 17 , 136 . Cancer is a leading cause of mortality worldwide 137 . Based on the structure and function of m 6 A-modified circRNA, researchers have found that they play an important role in the progression, proliferation and metastasis of cancers, such as colorectal cancer 128 , gastric cancer 129 , hepatocellular carcinoma (HCC) 130 , 131 and poorly differentiated gastric adenocarcinoma 132 .…”
Section: A-modified Circrna Associated With Pathophysiological Processesmentioning
confidence: 99%
“…Liver cancer has a high morbidity and mortality rate worldwide 137 . In HCC, circ_KIAA1429 (originate from KIAA1429) can accelerate the progress of HCC through the m 6 A-YTHDF3-Zeb1 mechanism, and may be a potential target for the HCC therapy 131 .…”
Section: A-modified Circrna Associated With Pathophysiological Processesmentioning
confidence: 99%